Manipulation of planar oxygen defect arrangements in multifunctional magnèli titanium oxide hybrid systems: from energy conversion to water treatment. Issue 12 (6th November 2020) - Liu, Yichen; Yang, Jack; Liu, Yang; Zheng, Jian; Lee, Wen; Shi, Junjie; Horlyck, Jonathan; Xie, Jiangzhou; Tay, Yee Yan; Tan, Thiam Teck; Yu, Dehong; Mole, Richard; et al.
Abstract : This work demonstrates that the layer structured Magnèli titanium oxides possess co-existing functionalities, which can be applied to both energy harvesting and water treatment using one material. Abstract : An extremely close relationship exists between energy usage and water supply with a tremendous amount of energy being consumed to process water for drinking and other purposes. The current energy crisis and inefficient water management place enormous stress on the sustainability of our society and environment. As such, the development of high-efficiency, cost-effective, and environmentally friendly materials which possess co-existing functionalities for applications ranging from energy capture to water treatment in one material, provides an opportunity to achieve sustainable development. As multifunctional materials, the layer-structured Magnèli titanium oxides with stoichiometry of Ti n O2 n −1 ( n ≥ 2) have been extensively studied in view of their potential for photocatalytic, thermoelectric and photothermal applications over the past few years. This group of materials occurs naturally as layered structures with planar oxygen defects, however, understanding of the correlation between the planar arrangements of the oxygen defects and various energy-related properties remains limited. Here, we demonstrate how the formation of layer structured Ti n O2 n −1 with various planar oxygen defect arrangements correlates with the changes of their physical and chemical properties. The experimental results from inelastic neutron scattering analysis and electrical characterizations provide evidence that the planar oxygen defects are responsible for phonon scattering and exert a strong influence on their electrical conductivities. Manipulating these planar defects allows interconversion between different phases, which changes the interplay between electronic and phononic sub-systems. These manipulations potentially enable optimization of the corresponding physical properties of these materials such that they are rendered suitable for applications that require co-operative multifunctionality. More specifically, the experimental results demonstrate that the valence band positions and the onset potentials in the materials are raised, further enhancing their ability for catalysis of electrochemical reactions. This work also demonstrates the combinational effects of the thermoelectric and photothermal properties of these materials on their photocatalytic and electrochemical performance thereby providing a novel means of controlling the multi-response functionality of these materials for a variety of applications in different environments.